2017
DOI: 10.1021/acs.molpharmaceut.7b00177
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Structure and Function of Polymeric Drug Delivery Nanoparticles Using Microfluidics

Abstract: We demonstrate control of multiscale structure and drug delivery function for paclitaxel (PAX)-loaded polycaprolactone-block-poly(ethylene oxide) (PCL-b-PEO) polymeric nanoparticles (PNPs) via synthesis and flow-directed shear processing in a two-phase gas-liquid microfluidic reactor. This strategy takes a page from the engineering of commodity plastics, where processing rather than polymer chemistry provides an experimental handle on properties and function. PNPs formed from copolymers with three different PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(89 citation statements)
references
References 69 publications
4
84
1
Order By: Relevance
“…This result showed that the on‐chip flow rate hold the potential for tuning timed release of specific drugs for desired treatments. In a more recent work of Moffitt's group, the effects of PCL block lengths and flow rate on sizes, morphologies, and PTX‐loading efficiencies of PCL‐ b ‐PEO micelles were studied systematically.…”
Section: Microfluidics For Fabrication Of Sddss With Well‐controlled mentioning
confidence: 99%
“…This result showed that the on‐chip flow rate hold the potential for tuning timed release of specific drugs for desired treatments. In a more recent work of Moffitt's group, the effects of PCL block lengths and flow rate on sizes, morphologies, and PTX‐loading efficiencies of PCL‐ b ‐PEO micelles were studied systematically.…”
Section: Microfluidics For Fabrication Of Sddss With Well‐controlled mentioning
confidence: 99%
“…14 Although the hydrolytic degradation of PCL makes it an appropriate in vivo host for a wide variety therapeutic molecules, its semicrystalline nature can strongly influence drug delivery properties. 15,16 For example, an increase in the crystallinity of the core-forming PCL blocks has been shown to increase drug release times in some studies. [15][16][17][18] However, crystallites can also exclude drug molecules leading to lower encapsulation efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 For example, an increase in the crystallinity of the core-forming PCL blocks has been shown to increase drug release times in some studies. [15][16][17][18] However, crystallites can also exclude drug molecules leading to lower encapsulation efficiencies. 15,16,18 In addition, SN-38 generally shows low solubility in aliphatic polyesters including PCL and PLGA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug‐loaded hydrogels can be directly injected in a minimally invasive way, thanks to their high moldability, and the ability to form tissue constructs in‐situ . Particularly interesting is the use of external stimuli to trigger the release of the drug at a specific site or specific time …”
Section: Introductionmentioning
confidence: 99%